RGD and BMP-2 mimetic peptide crosstalk enhances osteogenic commitment of human bone marrow stem cells. (May 2016) - Bilem, I.; Chevallier, P.; Plawinski, L.; Sone, E.D.; Durrieu, M.C.; Laroche, G.
Graphical abstract: Abstract: Human bone marrow mesenchymal stem cells (hBMSCs) commitment and differentiation are dictated by bioactive molecules sequestered within their Extra Cellular Matrix (ECM). One common approach to mimic the physiological environment is to functionalize biomaterial surfaces with ECM-derived peptides able to recruit stem cells and trigger their linage-specific differentiation. The objective of this work was to investigate the effect of RGD and BMP-2 ligands crosstalk and density on the extent of hBMSCs osteogenic commitment, without recourse to differentiation medium. RGD peptide promotes cell adhesion via cell transmembrane integrin receptors, while BMP-2 peptide, corresponding to residues 73–92 of Bone Morphogenetic Protein-2, was shown to induce hBMSCs osteoblast differentiation. The immobilization of peptides on aminated glass was ascertained by X-ray Photoelectron Spectroscopy (XPS), the density of grafted peptides was quantified by fluorescence microscopy and the surface roughness was evaluated using Atomic Force Microscopy (AFM). The osteogenic commitment of hBMSCs cultured on RGD and/or BMP-2 surfaces was characterized by immunohistochemistry using STRO-1 as specific stem cells marker and Runx-2 as an earlier osteogenic marker. Biological results showed that the osteogenic commitment of hBMSCs was enhanced on bifunctionalized surfaces as compared to surfaces containing BMP-2, while on RGD surfaces cells mainly preserved their stemness character. These results demonstrated that RGD and BMP-2 mimetic peptides act synergistically to enhance hBMSCs osteogenesis without supplementing the media with osteogenic factors. These findings contribute to the development of biomimetic materials, allowing a deeper understanding of signaling pathways that govern the transition of stem cells towards the osteoblastic lineage. Statement of Significance: For a long time, scientists thought that the differentiation of Mesenchymal Stem Cells (MSCs) into bone cells was dictated by growth factors. This manuscript shed light on other ligands that play a crucial role in regulating MSCs fate. In concrete terms, it was demonstrated that the osteoinductive effect of BMP-2 peptide is 2 folds improved in the presence of adhesive RGD peptide. Compared to previous works highlighting this synergistic cooperation between RGD and BMP-2 peptides, the main strength of this work lies to the use of primitive human cells (hMSCs) and well-defined biomimetic material surfaces (controlled surface roughness and peptide densities). This work provides valuable insights to develop custom-designed in vitro cell culture models, capable of targeting the desired cell response.